2009
DOI: 10.1037/0096-1523.35.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Feature integration theory revisited: Dissociating feature detection and attentional guidance in visual search.

Abstract: In feature integration theory (FIT; A. Treisman & S. Sato, 1990), feature detection is driven by independent dimensional modules, and other searches are driven by a master map of locations that integrates dimensional information into salience signals. Although recent theoretical models have largely abandoned this distinction, some observed results are difficult to explain in its absence. The present study measured dimension-specific performance during detection and localization, tasks that require operation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(101 citation statements)
references
References 59 publications
(99 reference statements)
13
84
3
Order By: Relevance
“…This is indeed what the present results show, as do those of Theeuwes et al (2006) and those of Mortier et al (2005). Furthermore, our account is in line with the recent findings of Chan and Hayward (2009). They found a crossdimensional cost in a detection task but not in a localization task or in a compound task.…”
Section: Discussionsupporting
confidence: 82%
“…This is indeed what the present results show, as do those of Theeuwes et al (2006) and those of Mortier et al (2005). Furthermore, our account is in line with the recent findings of Chan and Hayward (2009). They found a crossdimensional cost in a detection task but not in a localization task or in a compound task.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast with previous studies that employed this method (Nozawa, Reuter-Lorenz, & Hughes, 1994;Patching & Quinlan, 2004;Townsend & Nozawa, 1995), in the present experiments, we investigated how dimensional feature contrast signals are processed in visual search for feature singletons, according to saliency summation (e.g., Wolfe, 1994) or alternative models (e.g., serial checking, Chan & Hayward, 2009;Treisman & Gelade, 1980). Second, instead of requiring observers to make a simple manual response to the onset of one stimulus presented at a fixed location (Patching & Quinlan, 2004;Townsend & Nozawa, 1995) or saccade to a target stimulus presented at one of two possible locations (Nozawa et al, 1994), in the present study, the redundant-signals paradigm was implemented in a visual-search task in which a detection response had to be given if one (target) item differed from the surrounding (distractor) items in one or two dimensions (similar to Krummenacher et al, 2001, and Turatto et al, 2004.…”
Section: Methodsmentioning
confidence: 97%
“…Such a double-check strategy would result in increased RTs on single-target trials, provided that it takes longer, statistically, to determine the absence of a signal in a channel as compared with its presence, which is the norm in the relevant pop-out search studies (e.g., Found & Müller, 1996;Treisman & Gormican, 1988; see also Chun & Wolfe, 1996). Indeed, FIT (Treisman & Gelade, 1980;Treisman & Gormican, 1988; see also Chan & Hayward, 2009) assumes detection of singletons to involve a serial process of checking for activity in dimensional modules. Consequently, serial exhaustive search of dimensional modules has to be considered as an alternative to saliency summation models.…”
Section: Overview Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that in visual search and change detection experiments, identification is dependent on localization (Treisman & Gelade, 1980;Treisman & Gormican, 1988;Dukewich & Klein, 2009;Ghorashi et al, 2010;Busch et al, 2010a;Schneider & Wascher, 2013;Chan & Hayward, 2009;Watanabe, 2003;Wolfe et al, 2006;Agostinelli et al, 1986;Becker et al, 2000;Hughes et al, 2012). Thus, Experiment 2 investigated whether change detection without localization also implies a failure to identify the changing feature.…”
Section: Discussionmentioning
confidence: 99%